KUNINGAN REGENCY GOVERNMENT POLICY ON THE CIRCULATION OF EXPIRED FOOD - Malik Fidale, Faisal; Marlina, Tina; Harmono (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
Consumer Protection is any effort that guarantees legal certainty to protect consumers against expired food. This study aims to explore policies and legal protections for consumers related to expired foods, as well as the efforts that consumers can take in dealing with them. In this study, the author uses a normative juridical approach, which is a method of literature law research which is carried out by researching library materials or secondary data. Then it was continued with the collection of data on secondary legal materials obtained from literature studies in the form of law books, legal journals, and other literacy associated with the core of this research. Verification of tertiary legal materials obtained from law dictionaries, Indonesian Language dictionaries, and other dictionaries. This research can provide new insights for legal practitioners and judges in developing civil law. In addition, the study also promotes a better understanding of the role of the local government in Kuningan Regency in improving consumer protection and overcoming barriers such as public mindset, buyer negligence, lack of knowledge about expired food, and inadequate legal supervision.